Normal Strain

1. The problem statement, all variables and given/known data
ε = xe-x2
L = L

2. Relevant equations

ε = ΔL/L

3. The attempt at a solution

xe-x2 = (ΔL – L)/L

∴ ΔL = Lxe-x2 + L

I really don’t understand how the solution got "dx" on the first step, also the delta L. I want to understand the first step, the rest of the solution I understand. Thanks!

Attached Images
File Type: png Solution.png (26.2 KB)

http://ift.tt/1gdZJ5J

Leave a comment

Your email address will not be published.


*


Show Buttons
Hide Buttons